The Implementation of Translanguaging in English language Learning Video - Nuryogawati, Firly (English Language Teaching for EFL Learners Journal, 2024)
In this study, the researcher showed translanguaging implementation in the instructor's explanation in the English learning video on one YouTube channel and classified them according to Iversen's theory (2019). The researcher used content analysis to observe the three English learning videos on the GIA Academy. According to the report, the application of translanguaging in the three English learning videos evaluated is that the teacher utilizes translanguaging approaches that vary according to demands. Translanguaging is utilized in three English learning videos to explain each brief visual of the information in the form of PowerPoint to explain the subchapter, which is highly complicated learning content. The researcher also provided feedback on why the instructor applied translanguaging as one of the English learning strategies.